Inovasi Kurikulum dalam Pembentukan Karakter Peserta Didik Melalui Pengembangan Kurikulum Muatan Lokal Aswaja - Suhendar, Asep (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
This research aims to explain innovative approaches in character building of students through the development of the local content curriculum of Aswaja (Ahlussunnah wal Jama'ah) at SMK Al-Falah Nagreg. The local content of Aswaja is an essential component in Islamic education that aims to integrate Islamic values and teachings of Ahlussunnah wal Jama'ah into the school curriculum. This study focuses on how the development of the Aswaja local content curriculum can be an effective tool in shaping students' character. The research method used is qualitative analytical research with a descriptive qualitative approach. The results show that innovation in developing the Aswaja local content curriculum can significantly contribute to shaping students' character. Some important findings include: the integration of Islamic values, the development of spirituality, the formation of Islamic identity, the strengthening of tolerance and harmony, and community participation. This curriculum also encourages students' participation in social and community activities oriented towards Aswaja values. This research illustrates the importance of innovation in developing the Aswaja local content curriculum as an effective means in shaping students' character. These results have positive implications for improving the quality of Islamic education and forming a generation with noble character and responsibility in society.